Quantified mitral regurgitation and left atrial function in heart failure with reduced ejection fraction: interplay and outcome implications. (26th January 2022) - Malagoli, Alessandro; Rossi, Luca; Zanni, Alessia; Sticozzi, Concetta; Piepoli, Massimo F.; Benfari, Giovanni
Abstract : Aims: The clinical and prognostic importance of functional mitral regurgitation (FMR) in heart failure patients with reduced ejection fraction (HFrEF) has been highly debated. This study aims to define FMR linkage to cardiovascular (CV) outcomes and the interplay with left atrial (LA) function in a prospective cohort of consecutive HFrEF outpatients. Methods and results: Overall, 286 consecutive outpatients with chronic HFrEF were prospectively enrolled. FMR was quantified by effective regurgitant orifice area (EROA). Global peak atrial longitudinal strain (PALS) was measured by speckle tracking echocardiography. The primary endpoint was a composite of congestive heart failure hospitalization or CV death. During a mean follow‐up of 4.1 ± 1.5 years, the primary endpoint occurred in 99 patients (35%). The spline modelling of the risk by FMR severity showed an excess event risk starting at about the EROA value of 0.1 cm 2 . There was a remarkable graded association between the EROA strata, even if tested per 0.1 cm 2 increase, and the risk of CV events (hazard ratio [HR] EROA per 0.10 cm 2 increase: 1.42, 95% confidence interval [CI] 1.19–1.68; p < 0.0001). EROA ≥0.30 cm 2 was associated with CV events regardless of LA function (HR 2.34, 95% CI 1.29–4.19; p = 0.005). Less severe FMR (EROA ≥0.10 cm 2 ) was associated with a dismal outcome only in patients with reduced LA function (PALS <14%) (5‐year CV event rate 51 ± 4%); conversely, the risk of events was relative reduced when preserved global PALS and FMR coexisted (5‐year CV event rate 38 ± 6%). Conclusions: Our results refine the independent association between FMR and CV outcome among HFrEF outpatients. Within a moderate EROA range, LA function mitigates the clinical consequences of mitral regurgitation, providing measurable proof of the interplay between regurgitation and LA compliance.